2013
DOI: 10.1186/1471-2407-13-428
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal-type of differentiation predicts favourable overall survival: confirmatory clinicopathological analysis of 198 periampullary adenocarcinomas of pancreatic, biliary, ampullary and duodenal origin

Abstract: BackgroundPeriampullary adenocarcinomas comprise pancreatic, distal bile duct, ampullary and duodenal adenocarcinoma. The epithelia of these anatomical structures share a common embryologic origin from the foregut. With steadily increasing numbers of pancreatoduodenectomies over the last decades, pathologists, surgeons and oncologists are more often confronted with the diagnosis of “other than pancreatic” periampullary cancers. The intestinal subtype of ampullary cancer has been shown to correlate with better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 29 publications
10
69
0
2
Order By: Relevance
“…As reported in previous morphological studies[9,10], we observed overlap with the pancreatobiliary type also at the immunohistochemical level. As depicted in Fig 4A, tumors of the intestinal type co-expressed pancreatobiliary markers, such as CK7, CK17, MUC1, and MUC5AC, although to a lesser extent.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…As reported in previous morphological studies[9,10], we observed overlap with the pancreatobiliary type also at the immunohistochemical level. As depicted in Fig 4A, tumors of the intestinal type co-expressed pancreatobiliary markers, such as CK7, CK17, MUC1, and MUC5AC, although to a lesser extent.…”
Section: Discussionsupporting
confidence: 89%
“…Due to the intrinsic limitations in interobserver agreement linked to the assessment of hematoxylin-eosin stained slides, the current lack of reliable diagnostic criteria, especially when tumors show mixed or intermediate histological features[10,35,36], and to minimize design bias to predefined categories, a pure histomorphological classification based on hematoxylin-eosin staining was not addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Disease characteristics included site of primary (intrahepatic, hilar, distal bile duct, and gallbladder carcinoma) and disease stage according to the 7 th edition of the American Joint Committee (AJCC) on cancer staging system. Patients with carcinoma of the ampulla of Vater were excluded, as these are thought to behave differently to other cancers of the biliary tract [36]. Treatment modalities collected included surgery with curative intent (R0 [negative margins]/ R1 [microscopic positive margins]), chemotherapy or best supportive care.…”
Section: Methodsmentioning
confidence: 99%